FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN BPJS DI DESA PARGARUTAN TONGA KECAMATAN ANGKOLA TIMUR TAHUN 2017 - Hidayah, Arinil; Imsaruddin, Guntur (Universitas Aufa Royhan, 2017)
National Health Insurance Program organized by the Body Of Social Security Health is certainly going to run more maximal if accompanied by the quality of good health services provided by healthcare providers.The purpose of this study is to determine the Factors Associated With Utilization the Body Of Social Security In Pargarutan Tonga Village District East Angkola Year 2017. This study used descriptive method Correlation, With the research design is cross sectional. The research was conducted in Pargarutan Tonga Village, East Angkola District, with population of 199 people. The sample in this study amounted to 67 people. Taken by technique Simple random sampling card holder the Body Of Social Security. The instrument of this research is questionnaire.Based on the result of research, it can be concluded that there is a significant correlation between sex (p = 0.019), education (p = 0,000), health officer (p = 0,040), and perception of respondent (p = 0,003) with the Body Of Social Security utilization. However, there was no significant correlation between age (p = 0,176), work (p = 0,062), and house distance (p = 0,110) with the Body Of Social Security utilization.It is expected that people should pay more attention to their health and take advantage of the health provided by the Body Of Social Security